Amplifying the excited state chirality through self-assembly and subsequent enhancement via plasmonic silver nanowires. Issue 38 (23rd September 2020) - Fu, Kuo; Jin, Xue; Zhou, Minghao; Ma, Kai; Duan, Pengfei; Yu, Zhen-Qiang
Abstract : Chiral luminescence of chiral emitters is enhanced through self-assembly, and subsequently was enhanced by plasmonic silver nanowires. Abstract : The development of circularly polarized luminescent materials with a large luminescence dissymmetry factor ( g lum ) is continuing to be a big challenge. Here, we present a general approach for amplifying circular polarization of circularly polarized luminescence (CPL) through intergrating molecular self-assembly and surface plasmon resonance (SPR). Molecular self-assembly could amplify the CPL performance. Subsequently, the composites built of nanoassemblies and achiral silver nanowires (AgNWs) show intense CPL activity with an amplified g lum value. By applying an external magnetic field, the CPL activity of the nanoassemblies/AgNWs composites has been significantly enhanced, confirming a plasmon-enhanced circular polarization. Our design strategy based on SPR-enhanced circular polarization of the chiral emissive systems suggests that combining plasmonic nanomaterials with chiral organic materials could aid in the development of novel CPL active nanomaterials.